2012
DOI: 10.1016/j.hrthm.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Regional cooling facilitates termination of spiral-wave reentry through unpinning of rotors in rabbit hearts

Abstract: BACKGROUND Moderate global cooling of myocardial tissue was shown to destabilize 2-dimensional (2-D) reentry and facilitate its termination. OBJECTIVE This study sought to test the hypothesis that regional cooling destabilizes rotors and facilitates termination of spontaneous and DC shock-induced subepicardial reentry in isolated, endocardially ablated rabbit hearts. METHODS Fluorescent action potential signals were recorded from 2-D subepicardial ventricular myocardium of Langendorff-perfused rabbit heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
3
23
0
5
Order By: Relevance
“…And at lower temperature (deeper hypothermia 5.9 • C ± 1.3 • C), local cooling facilitates termination of spiral waves [54]. The latter two studies [54,53] showed the positive effect of hypothermia in macro / organ scale.…”
Section: Resultsmentioning
confidence: 90%
“…And at lower temperature (deeper hypothermia 5.9 • C ± 1.3 • C), local cooling facilitates termination of spiral waves [54]. The latter two studies [54,53] showed the positive effect of hypothermia in macro / organ scale.…”
Section: Resultsmentioning
confidence: 90%
“…En el ámbito de la electrofisiología cardíaca se han realizado trabajos en los que con diferentes propósitos se introducen modificaciones mediante fármacos [Yashima et al 1999, Milberg et al 2005, Hsieh et al 2009a] o agentes físicos, tales como estiramiento , Bode et al 2006], temperatura [Harada et al 2008, Hsieh et al 2009b, Yamazaki et al 2012), o estímulos eléctricos, alterando la electrofisiología de las preparaciones experimentales. El análisis de los efectos de estos cambios sobre los parámetros electrofisiológicos del miocardio y la dinámica del frente de onda, puede proporcionar información valiosa que permita explicar en parte los mecanismos de generación, perpetuación o cese de las arritmias.…”
Section: Electrofisiología Experimental Y Temperaturaunclassified
“…No obstante, muy recientemente otro grupo de investigación ha realizado trabajos similares empleando sistemas ópticos conjuntamente con dispositivos traslúcidos desarrollados al efecto [Yamazaki et al 2012].…”
Section: Desarrollo De Dispositivos Ad Hoc 171 Justificación De La unclassified
See 2 more Smart Citations